2007
DOI: 10.2105/ajph.2006.106047
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in the Development of Disability Among Older Adults

Abstract: Objective-This study investigates differences in developing activities of daily living (ADL) disability among non-Hispanic Whites, African Americans, Hispanics interviewed in Spanish (Hispanic/Spanish), and Hispanics interviewed in English (Hispanic/English) Methods-Six-year risk for disability development is estimated from 8161 participants age 65 or older free of baseline disability in a population-based sample. Mediating factors amenable to clinical and public health intervention on racial/ethnic difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 47 publications
(60 reference statements)
8
75
4
Order By: Relevance
“…Like sleep complaints, disability is common in older adults, with approximately 35%-50% of older adults having some difficulties with activities of daily living. Consistent with previous studies, 34,35 there was an increased burden of disability among African Americans. Further, sleep was a predictor of disability in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Like sleep complaints, disability is common in older adults, with approximately 35%-50% of older adults having some difficulties with activities of daily living. Consistent with previous studies, 34,35 there was an increased burden of disability among African Americans. Further, sleep was a predictor of disability in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to studies that report ethnic disparities in disability, [4][5][6][7][8][9] we found that risks of functional limitations were generally similar between non-Hispanic Blacks, Mexican Americans, and non-Hispanic Whites after adjustment for demographic characteristics-including education level and poverty index-and disease burden. Similar findings were recently reported by Song et al using data from the Health and Retirement Study.…”
Section: Research and Practicecontrasting
confidence: 99%
“…Musculoskeletal conditions, chronic neurological and cardiopulmonary disorders, sensory and cognitive deficits, anemia, sarcopenia, and chronic pain may lead to functional limitations and disability. Many of the chronic health conditions that can affect physical functioning are more common among ethnic minorities and economically disadvantaged groups, 5,6,[9][10][11][12] raising the question of whether a greater burden of disease can primarily explain the higher prevalence of functional limitations and disability in these groups. Previous studies of socioeconomic and ethnic disparities in functional limitations reported unadjusted data or data adjusted only for differences in demographic characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, the explanatory role of color/race in the functional decline of elderly is controversial. In the United States, race explains functional decline in the elderly, even after adjusting for socioeconomic variables 29,38 . However, in England and Brazil this association has still not been observed 6,9,16 .…”
Section: Discussionmentioning
confidence: 99%